Involving Local Wisdom as Values to Develop English for Tourism Course Material: A Case of Baduy Tribe in Lebak Banten - Welliam Hamer; Sutrisno Sadji Evenddy; Jumbuh Prabowo; Rosmania Rima; Dhafid Wahyu Utomo (Journal of English Language Studies, 2017)
This study aims at developing course material of English for Tourism material involving the values local wisdom at English Department Untirta. In specific, this study has the objectives to (1) determine the current materials, (2) provide the materials for EFT which are appropriate to the needs of students and stakeholders by involving local wisdom of Baduy tribe. This study carried out in Serang and Lebak Regency. This study uses research and development methodology (R&D). The data collecting techniques in this study are documentation, questionnaire, and interview. The data gained from documentation and interview analyzed by using content analysis. While the data gained from questionnaire were analyzed quantitatively. The conclusions are (1) The running materials of English for Tourism are based on lecturer’s assumption, (2) Based on the expert  validation, the model material of English for Tourism falls into very feasible category with the percentage of 86.76 %. The teaching material based on the results of the students’ responses by the percentage is in the category of good (78.9 %). Based on the validation both from expert and students it could be concluded that an EFT material involving Baduy local wisdom was feasible to be applied in English Department of Sultan Ageng Tirtayasa University. Keywords: material development, English for tourism, local wisdom, Baduy Tribe